Sustainable development goals their impacts on forests and people - Katila, Pia ca. 20./21. Jh; Winkel, Georg 1975-; Pacheco, Pablo; Galloway, Glenn ca. 20./21. Jh; Jong, Wil de 1956-; Colfer, Carol J. Pierce 1945- (Cambridge University Press, 2020)
Forests provide vital ecosystem services crucial to human well-being and sustainable development, and have an important role to play in achieving the seventeen Sustainable Development Goals (SDGs) of the United Nations 2030 Agenda. Little attention, however, has yet focused on how efforts to achieve the SDGs will impact forests and forest-related livelihoods, and how these impacts may, in turn, enhance or undermine the contributions of forests to climate and development. This book discusses the conditions that influence how SDGs are implemented and prioritised, and provides a systematic, multidisciplinary global assessment of interlinkages among the SDGs and their targets, increasing understanding of potential synergies and unavoidable trade-offs between goals. Ideal for academic researchers, students and decision-makers interested in sustainable development in the context of forests, this book will provide invaluable knowledge for efforts undertaken to reach the SDGs. This title is available as Open Access via Cambridge Core
Title from publisher's bibliographic system (viewed on 18 Dec 2019)
Keywords: Sustainable Development Goals; Sustainable forestry; Sustainable development